Determination of the mass-transfer coefficient in designing heterogenous catalytic processes - Пономаренко, Анна Владимировна; Ведь, Валерий Евгеньевич (Eastern-European Journal of Enterprise Technologies, 2014)
Description of mass-transfer heterogeneous catalytic processes based on the experimental data, obtained when studying the thermocatalytic benzene vapor destruction reaction on the solid catalyst of the Со3О4/α-Al2O3 system is performed. The dependences of mass-transfer coefficient on such parameters as the phase contact time, the surface concentration of the catalytically active component on the carrier, and the initial hydrocarbon concentration in the gas flow are described. A method for calculating mass-transfer coefficient of heterogeneous catalytic conversion of gaseous impurities, which includes all the above parameters is proposed. Temperature dependences of mass-transfer coefficient of the studied process obtained based on the proposed method and experimental data, on the phase contact time, the surface concentration of the catalytically active component on the carrier, and the value of the initial benzene vapor concentration in the gas flow are built. The adequacy of the obtained mathematical dependence is confirmed by computational methods that allows to use it for intensifying the mass-transfer processes during heterogeneous catalytic reactions in catalytic converters.